209k views
1 vote
Which of the following shows why 613 is equivalent to 6–√3?

Which of the following shows why 613 is equivalent to 6–√3?-example-1
User Zearin
by
4.8k points

1 Answer

4 votes

Answer:

D

Explanation:

Given:

6^1/3 is equivalent to 3√6

Let

k = 1/3

6^k = 3√6

Cube both sides of the equation

(6^k)^3 = (3√6)^3

(3√6)^3 ( cube root cancel power cube (

6^3k = 6^1

They both have the same base, so it cancels out

3k = 1

Divide both sides by 3

k = 1/3

Therefore, option D shows why 6^1/3 is equivalent to 3√6

User Piero Borrelli
by
4.6k points